Communication Strategy of Directorate General of Tax to Increase Tax Revenue During the Covid-19 Pandemic - Zamzam, Azulla; Hastjarjo, Sri; Slamet, Yulius (KnE Social Sciences, 2022)
The decrease in economic growth due to the Covid-19 pandemic has resulted from several problems, including a decrease in tax revenues which are a source of state revenue. This study poposed to examine the communication strategy of the Directorate General of Tax which aimed to disseminate information related to changes in the tax service system to ensure that tax revenue remained on target. During the Covid-19 pandemic, information has been distributed through communication channels such as social media, websites and applications. This study used qualitative methods and data were collected by conducting interviews with selected informants recruited through purposive sampling. Triangulation was used to test the validity of the data. In this study, Hafied Cangara’s communication strategy planning model of Assessment, Communication and Analysis, Design, and Action (ACADA) was used. According to the results, the Directorate General of Tax issued a communication strategy by disseminating information from the center to tax office units, maximizing information dissemination through social media, creating educational tutorial content related to taxes, and collaborating with influencers to participate in the tax counseling process. Keywords: communication strategy, tax revenue, Covid-19 pandemic, society 5.0